Phân tích nguyên nhân gây sụt lở mặt đất ở Cam Lộ (Quảng Trị) - Canh, Nguyễn Văn; Thanh, Nguyễn; Tuấn, Nguyễn Quang; Hưng, Nguyễn (Vietnam Journal of Earth Sciences, 2007)
Determining causes of ground collapse at Cam Lo, Quang Tri province